The Pro-197-Thr mutation in the ALS gene confers novel resistance patterns to ALS-inhibiting herbicides in Bromus japonicus in China - Liu, Leicheng; Wu, Lamei; Li, Zongfang; Fang, Yuhang; Ju, Boming; Zhang, Sisi; Bai, Lianyang; Pan, Lang (Frontiers in Plant Science, 2024)
Bromus japonicus is one of the most notorious agricultural weeds in China. The long-term use of ALS-inhibiting herbicides has led to rapid evolution of herbicide resistance in B. japonicus. In the present study, a B. japonicus population (BJ-R) was confirmed to be 454- and 2.7-fold resistant to the SU herbicides mesosulfuron-methyl and nicosulfuron, and 7.3-, 2.3-, 1.1- and 10.8-fold resistant to the IMI herbicide imazamox, the TP herbicide penoxsulam, the PTB herbicide pyribenzoxim and the SCT herbicide flucarbazone-sodium, respectively, compared with its susceptible counterpart (BJ-S) through dose‒response experiments. Neither a P450 inhibitor nor a GST inhibitor could reverse the level of resistance to mesosulfuron-methyl in BJ-R. In addition, no significant differences in GST activity were found between the BJ-R and BJ-S. ALS gene sequencing revealed a Pro-197-Thr mutation in BJ-R, and the gene expression had no significant differences between the BJ-R and BJ-S. The ALS activity of BJ-R was 106-fold more tolerant to mesosulfuron-methyl than that of BJ-S. Molecular docking showed that the binding energy of the ALS active site and mesosulfuron-methyl was changed from -6.67 to -4.57 kcal mol-1 due to the mutation at position 197. These results suggested that the Pro-197-Thr mutation was the main reason for the high resistance level of BJ-R to mesosulfuron-methyl. Unlike previous reports of the cross-resistance pattern conferred by this mutation, we firstly documented that the Pro-197-Thr mutation confers broad cross-resistance spectrums to ALS-inhibiting herbicides in B. japonicus.